Experimental and numerical investigations on seismic behavior of hybrid braced precast concrete shear walls. (1st November 2019) - Li, Hong-Nan; Tang, Ya-Chao; Li, Chao; Wang, Li-Ming
Highlights: Two types of innovative hybrid BPCS walls are proposed. Pseudo-static tests of six BPCS wall and one MCS wall are conducted. The failure mode and hysteretic property of BPCS walls are investigated. Effects of bracing and SSR on seismic behavior of BPCS walls are evaluated. Abstract: This paper experimentally and numerically investigates the seismic behavior of two innovative types of hybrid precast concrete shear walls with diagonal-shaped or cross-shaped concealed bracings. Six 0.75-scaled braced precast concrete shear (BPCS) wall specimens and one monolithic cast-in-situ shear (MCS) wall were fabricated and employed to conduct the displacement-controlled pseudo-static tests. The length and thickness of the specimens were identical, whereas the heights of BPCS wall specimens were different owing to the different shear span ratios (SSRs) of 1.0, 1.5 and 2.0. Using the MCS wall specimen as a reference, the effects of bracing type and SSR on the seismic behavior of BPCS walls were studied in terms of failure mode, hysteretic behavior and energy dissipation capacity. Finite element (FE) analyses of the wall specimens were further performed using the multi-layer shell element model on the Opensees platform. The numerically calculated hysteresis loops of the wall specimens show good agreement with the experimental data, which proves that the employed FE model is adequately accurate in the seismic behavior assessment of BPCS walls. The experimental and numerical results indicate that the developed BPCS walls not only possess similar bearing capacity but also outperform the MCS wall in saving concrete usage and enhancing energy dissipation capacity. The diagonal and cross BPCS walls exhibit diametrically opposite characteristics as SSR increases. The diagonal BPCS wall with low SSR of 1.0 performs better in drift capacity, while the cross BPCS walls are more suitable for earthquake resistance at higher SSRs of 1.5 and 2.0.